PENGARUH ARUS KAS OPERASI, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Angkotasan, Fadhil Fatih Fashalea; Atarwaman, Rita J.D.; Leatemia, Senda Yunita (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to examine the effect of Operating Cash Flow, Company Size, and Leverage on Company Value in basic industrial and chemical sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This study is a quantitative study. The data in this study is secondary data obtained from the Indonesia Stock Exchange website, namely www.idx.co.id. The population in this study is 77 companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample in this study is 60 companies that have met the criteria. The data analysis method in this study used multiple linear regression analysis. The results of this study show that Operating Cash Flow, and Company Size have a significant positive effect on Company Value, while Leverage has a significant negative effect on Company Value in Basic Industrial and Chemical Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the period (2019-2021)